Perbandingan Penyelesaian Sengketa Perceraian Secara Mediasi di Pengadilan dan di Luar Pengadilan di Kabupaten Kampar - Rika Lestari (Jurnal Hukum IUS QUIA IUSTUM, 2014)
The problems studied in this research were: first, how is a divorce settlement through mediation in Religious Court of Bangkinang, Kampar Regency? Second, how is a divorce settlement through mediation outside the court of Kampar Regency? Third, what are the advantages and disadvantages of a divorce settlement through mediation outside and inside the court of Kampar Regency? The method used in this study was juridical sociological. The result concluded that first, the divorce settlement through mediation in Religious Court of Bangkinang had not yet optimally conducted. Second, the divorce settlement through mediation outside the court of Kampar Regency might take place due to good emotional bound between the parties in dispute and the mediators. Third, the advantages of the mediation process in divorce settlement in the court of Kampar Regency were confidential, low cost, and the existence of family spirit. Meanwhile, the disadvantages were the embarassment to the older members of the family and the indirect way of problem solving in which the elders dominantly put their opinions more than the parties in dispute. Moreover, the schedule to meet was uncertain because it needed to be synchronized to the schedules of the elders of each party in dispute. Also, there was no sytematic recording since it was usually conducted verbally.